INTRAVITREAL DEXAMETHASONE IMPLANT FOR RADIATION MACULOPATHY SECONDARY TO PLAQUE BRACHYTHERAPY IN CHOROIDAL MELANOMA. Issue 9 (September 2015) - Caminal, José M.; Flores-Moreno, Ignacio; Arias, Luis; Gutiérrez, Cristina; Piulats, Josep M.; Català, Jaume; Rubio, Marcos J.; Cobos, Estefanía; García, Pere; Pera, Joan; Giralt, Joan; Arruga, Jorge
Abstract : Purpose: To evaluate the efficacy of intravitreal dexamethasone implant 0.7 mg (Ozurdex) in radiation maculopathy secondary to plaque brachytherapy in choroidal melanoma. Methods: Twelve eyes diagnosed of radiation maculopathy secondary to plaque brachytherapy and treated with intravitreal dexamethasone implant were included. Visual acuity, foveal thickness using spectral domain optical coherence tomography, and grade of macular edema, using Horgan classification, were evaluated. Results: Mean age was 65.5 ± 28 years (range, 40–82 years). Mean follow-up was 8.2 ± 7.8 months (range, 2–28 months). Mean visual acuity before treatment was, in logarithm of the minimum angle of resolution scale, 1 ± 0.58 (range, 0.4–2) and mean final visual acuity 0.8 ± 0.58 (range, 0.2–2), showing a nonsignificant trend to improvement ( P = 0.091; Wilcoxon's test). Foveal thickness before treatment was 416 ± 263 μ m (range, 222–725 μ m) and final foveal thickness 254 ± 170 μ m (range, 145–750), showing a significant decrease ( P = 0.016; Wilcoxon's test). Referring to Horgan classification, a significant reduction in grades before and after treatment was demonstrated ( P = 0.007; Wilcoxon's test). Conclusion: Ozurdex is a useful treatment for radiation maculopathy associated to plaque brachytherapy for uveal melanoma, with a significant decrease in foveal thickness and a significant improvement in Horgan classification. This anatomical improvement was correlated with a moderate improvement in visual acuity. Abstract : Intravitreal dexamethasone implant is a useful treatment for radiation maculopathy secondary to plaque brachytherapy in choroidal melanoma. A decrease in foveal thickness was demonstrated during the follow-up of patients.